Differences in the Establishment of Gut Microbiota and Metabolome Characteristics Between Balb/c and C57BL/6J Mice After Proton Irradiation - Li, Yuchen; Sui, Li; Zhao, Hongling; Zhang, Wen; Gao, Lei; Hu, Weixiang; Song, Man; Liu, Xiaochang; Kong, Fuquan; Gong, Yihao; Wang, Qiaojuan; Guan, Hua; et al. (Frontiers in Microbiology, 2022)
Although proton irradiation is ubiquitous in outer space as well as in the treatment of human diseases, its effects remain largely unclear. This work aimed to investigate and compare the composition of gut microbiota composition of mice in different species exposed to high-dose radiation. Male Balb/c mice and C57BL/6J mice were irradiated at a high dose (5Gy). Fecal specimens before and after irradiation were subjected to high-throughput sequencing (HTS) for the amplification of 16S rRNA gene sequences. We observed substantial changes in gut microbial composition among mice irradiated at high doses compared to non-irradiated controls. The changes included both the alpha and beta diversities. Furthermore, there were 11 distinct alterations in the irradiation group compared to the non-radiation control, including the families Muribaculaceae, Ruminococcaceae, Lactobacillus, Lachnospiraceae_NK4A136, Bacteroides, Alistipes, Clostridiales, Muribaculum, and Alloprevotella. Such alterations in the gut microbiome were accompanied by alterations in metabolite abundances, while at the metabolic level, 10 metabolites were likely to be potential biomarkers. Some alterations may have a positive effect on the repair of intestinal damage. Simultaneously, metabolites were predicted to involve multiple signal pathways, such as the tricarboxylic acid cycle and glycogen synthesis, aerobic respiration, sucrose degradation III. Metabolites produced by proton irradiation in the microbial region play a positive role in repairing damage, which makes this area worthy of further experimental exploration. The present work offers an analytical and theoretical foundation to investigate how proton radiation affects the treatment of human diseases and identifies potential biomarkers to address the adverse effects of radiation.